Historiography and Identity. (Turnhout, Belgium)
6. cilt (xii, 468 sayfa)
Keywords: “The volume discusses Central European and Eastern Central European historiographies of the High and Late Middle Ages. It deals with histories written in a time which brought about a profound differentiation of medieval societies in these regions. As new social classes achieved economic and political power, the demand for reassuring identifications grew more pressing. Narratives of the past were tailored specifically for distinct social groups, often using vernacular languages instead of the universal language of elite education, Latin. The volume pays attention to the interplay between languages and focuses on the strategies that individual works developed in order to balance the many alternative modes of identification. Filling a significant scholarly gap, the volume offers important insights into narratives of identification written in Latin and in the various vernaculars emerging as the new political languages of the period.” --